Changes in the Conformational State of Hemoglobin in Hemodialysed Patients with Chronic Renal Failure. (18th March 2015) - Pieniazek, Anna; Gwozdzinski, Krzysztof
Abstract : The aim of this study was to evaluate the properties of internal components of erythrocytes in chronic renal failure (CRF) patients undergoing hemodialysis (HD) in comparison to control subjects. For investigation of conformational state of hemoglobin and nonheme proteins (NHP) the maleimide spin label (MSL) in electron paramagnetic resonance (EPR) was applied. The studies were performed using MSL in whole cells and hemolysate as well as proteins separated by ion exchange chromatography and checked by electrophoresis. Additionally the level of –SH groups in hemolysate and isolated internal proteins of CRF erythrocytes was determined using 4, 4′-dithiodipyridine. All measurements were performed before and after hemodialysis. Oxidative stress accompanying CRF/hemodialysed patients caused a significant decrease in the mobility of internal components inside erythrocytes indicated by MSL ( P < 0.02). The significant decrease in mobility of spin labeled HbA1c and HbA both before and after HD ( P < 0.0002) as well as in nonheme proteins before hemodialysis ( P < 0.05) versus control was indicated. Decrease in mobility of internal components of erythrocytes was accompanied by loss of thiols before and after hemodialysis versus control in NHP ( P < 0.05), HbA1c ( P < 0.0002), and HbA ( P < 0.0005). These findings showed oxidative influence of hemodialysis on hemoglobins and internal nonheme proteins in erythrocytes of CRF patients.